2008
DOI: 10.1007/s11606-008-0561-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Patterns of Health Care System Distrust Between Blacks and Whites

Abstract: Racial differences in health care system distrust are complex with far greater differences seen in the domain of values distrust than in competence distrust. This framework may be useful for explaining the mixed results of studies of race and health care-related distrust to date, for the design of future studies exploring the causes of racial disparities in health and health care, and for the development and testing of novel strategies for reducing these disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
209
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(222 citation statements)
references
References 47 publications
11
209
2
Order By: Relevance
“…Previous research has found that whites also report higher levels of trust in medical providers than nonwhites do. 21,22 Severity Of Injury Finally, consonant with results from previous studies, [11][12][13] we found that injury severity matters to patients' responses to error disclosure. Respondents considering serious-injury scenarios were significantly more likely than those considering nonsevere injuries to seek legal advice, change physicians, and view disclosures as motivated by the desire to avoid lawsuits, and were significantly less likely to accept offers.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has found that whites also report higher levels of trust in medical providers than nonwhites do. 21,22 Severity Of Injury Finally, consonant with results from previous studies, [11][12][13] we found that injury severity matters to patients' responses to error disclosure. Respondents considering serious-injury scenarios were significantly more likely than those considering nonsevere injuries to seek legal advice, change physicians, and view disclosures as motivated by the desire to avoid lawsuits, and were significantly less likely to accept offers.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, these pre-ESRD measures may still contribute to the disparate findings in mortality that we observed by race and level of neighborhood SES. Although the access to care may not differ among young adult patients residing in low SES neighborhoods, challenging psychosocial circumstances for low SES young blacks (such as experiences of social stigmatization and discrimination or poor health literacy) may lead to greater distrust in medical institutions, 45 potentially resulting in their underuse of available medical resources and lower medical adherence. 46 These factors may contribute to uncontrolled diabetes 47 and HIV 48 as well as greater rates of dialysis initiations with a catheter 49 and fewer conversions to arteriovenous access 50 among young blacks with low SES.…”
Section: Discussionmentioning
confidence: 99%
“…32 We selected a random sample of 845 individuals over the age of 18 who had been seen at a primary care practice or emergency department with the University of Pennsylvania Health System in the past 3 years. Individuals were eligible if they spoke English and were able to complete a 15-minute interview.…”
Section: Phase 3: Psychometric Analyses and Further Item Reductionmentioning
confidence: 99%
“…Responders were slightly more likely to be women, older and insured. 32 The telephone interviews were spread over days of the week and times of the day. The telephone interviewers were racially diverse, but no attempt was made to match respondent and interviewer race.…”
Section: Phase 3: Psychometric Analyses and Further Item Reductionmentioning
confidence: 99%